2018
DOI: 10.1007/s00267-018-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Decline of Traditional Practices in Communities from the Gwallek–Kedar area, Kailash Sacred Landscape, Nepal

Abstract: Traditional knowledge and practices are increasingly recognized in the resource conservation and management practices, however are declining in many parts of the world including Nepal. Studies on the inventory of traditional knowledge are available, albeit limited, and empirical analysis of factors contributing to the decline of traditional knowledge are negligible in Nepal. We thus initiated this study in the Nepal part of the Kailash Sacred Landscape to (i) document traditional knowledge and practices on agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…The most commonly used part is leaf gel, which is effective for treating cuts and burns, gastrointestinal disorders, and maintaining blood pressure. Jelly obtained from the leaf is used to treat cuts, burns, and other skin complaints in the Indian subcontinent [ 96 , 97 , 98 , 99 , 100 ]. It is also eaten by people suffering from high blood pressure, gastritis, and stomach-related diseases [ 96 ].…”
Section: Traditional Medicine Use Of Aloe Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used part is leaf gel, which is effective for treating cuts and burns, gastrointestinal disorders, and maintaining blood pressure. Jelly obtained from the leaf is used to treat cuts, burns, and other skin complaints in the Indian subcontinent [ 96 , 97 , 98 , 99 , 100 ]. It is also eaten by people suffering from high blood pressure, gastritis, and stomach-related diseases [ 96 ].…”
Section: Traditional Medicine Use Of Aloe Plantmentioning
confidence: 99%
“…Jelly obtained from the leaf is used to treat cuts, burns, and other skin complaints in the Indian subcontinent [ 96 , 97 , 98 , 99 , 100 ]. It is also eaten by people suffering from high blood pressure, gastritis, and stomach-related diseases [ 96 ]. In Sikkim-India, A. vera is used for its antihyperglycemic effect [ 101 ].…”
Section: Traditional Medicine Use Of Aloe Plantmentioning
confidence: 99%
“…The average annual income of the respondents was 25862.75 NRs (USD 253.75) which is very low than national per capita income (USD 682.22) [17]. Similar pattern of income of the respondents were found in the Nepalese Ruler communities [17,18]. The major income sources of respondents were agriculture, business, government job, wedges and remittances.…”
Section: Descriptive Information Of the Respondentsmentioning
confidence: 54%
“…Subsets of socio-economic factors such as settlement, population, family size, gender, age, ethnicity, education, economy, and occupation have effect on knowledge of plant use [19][20][21]. Studies have demonstrated that ethnobotanical knowledge increases with an individual's age [22] and length of residence [23].…”
Section: Introductionmentioning
confidence: 99%